Optimalisasi Peran Keluarga sebagai Pengawas Menelan Obat pada Pasien TB Paru - Ulva, Fadillah; Hikmi, Nailul (Universitas Alifah Padang, 2024)
Pulmonary TB control is influenced by the compliance of pulmonary TB patients in taking medication. Patient non-compliance in taking anti-tuberculosis drugs causes the incidence of pulmonary TB to still be high. Obstacles found in efforts to control pulmonary TB are inadequate treatment (dose, type, number of drugs and time period), the unavailability of adequate information about pulmonary TB for clients and families. Family involvement in the care of pulmonary TB patients determines the success of treatment. One of the family's roles is to monitor medication swallowing. Based on these problems, it is necessary to optimize the role of the family as supervisors of drug swallowing in pulmonary TB patients. The aim of the community service activities carried out is to increase the role of the family as supervisors of medication swallowing. Community service activities are carried out in the Andalas Health Center Work Area. The activities carried out are in the form of outreach aimed at increasing public understanding regarding the role of the family in supporting medication adherence in pulmonary TB patients. The targets of this activity are families and pulmonary TB patients. After carrying out community service activities, there was an increase in knowledge and awareness in the community regarding the role of the family as supervisors of pulmonary TB drug swallowing.